Peran Baby Massage Sebagai Stimulasi Nonfarmakologis Untuk Meningkatkan Berat Badan Bayi Usia 6 Bulan - Siti Fithrotul Umami (Universitas Pahlawan Tuanku Tambusai, 2025)
Weight is a crucial indicator in assessing infant development. Six-month-old infants are in the transition stage from exclusive breastfeeding to complementary feeding, thus requiring extra encouragement to support optimal growth. A non-pharmacological intervention that has been proven effective is infant massage. This research aims to explain the role of baby massage as a non-pharmacological stimulation in increasing the weight of six-month-old infants at the Ny.